MR image processing : segmentation of the brain in MRI - Li, Jia. (2008)
Accurate and fully automatic segmentation of brain from magnetic resonance (MR)scans is a challenging problem that has received an enormous amount of attention lately. In this dissertation, we present a robust fully automatic method for segmenting the brain from head magnetic resonance (MR)images. This method works well even in the presence of radio frequency (RF) in homogeneities. It is a combination of several existing image processing techniques such as anisotropic filters and Binary morphology.